Religion in the Thought of the Young Hegel - Dierken, Jörg (Religions, 2024)
Religion is one of the central themes of the young Hegel. This is where intellectual problems arise, the treatment of which led him to discover his speculative way of thinking. Starting in the footsteps of Kant’s ethicotheology, Hegel quickly realized that religion cannot be a vehicle for introducing autonomous morality. Under titles such as love and life, he then develops a kind of Spinozist thinking of unification of everything, including the finite and the infinite. However, it turns out that the quasi-divine performance of unity cannot be thought of as such, since thinking is bound to discursive forms of reflection that are always mediated through differences. As soon as the religious performance of unity is to be thought of, it slips away from the form of reflection. This problem can be solved if, on the one hand, the differential form of thinking is brought into a self-application and, on the other hand, difference itself is put into the performance of unity, even if it is named as absolute. The former becomes the nucleus of the figure of negation characteristic for Hegel’s speculative thinking; the latter leads to an understanding of the absolute as spirit, which, according to its self-being, which encompasses difference, is always for the other and is known by the other. Religion brings this to mind in the form of imagination, according to Hegel’s later concept of religion.